"On Water" Sonochemical Multicomponent Synthesis of Novel Bioactive 1, 1′-(Aryl)bis(2-(cyclohexylamino)-2-oxoethane-1, 1-diyl) Di(alkanoates and benzoates). (29th December 2013) - Mamaghani, Manouchehr; Mahmoodi, Nosrat O.; Shirini, Farhad; Azimi-Roshan, Abbas; Monfared, Azam
Abstract : An expeditious, efficient, and ecofriendly ultrasound-promoted synthesis of a series of novel 1, 1′-(aryl)bis(2-(cyclohexylamino)-2-oxoethane-1, 1-diyl) di(alkanoate and benzoate) derivatives (6a –k ), as useful building block candidates for natural products and drugs, is reported. The target compounds were prepared by the reaction of alkyl or aryl carboxylic acid, various bisaldehydes and isocyanocyclohexane in water using one-pot isocyanide-based multicomponent approach. This efficient protocol without using any catalyst furnished the products in short reaction times (4-5 min) and excellent yields (87–96%). The antibacterial activity of the selected products was also examined. Some products showed promising activities.